2012
DOI: 10.1016/j.jss.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Bone flap perfusion assessment using near-infrared fluorescence imaging

Abstract: Background Microsurgical vascularized bone flaps are a versatile technique for reconstructing large bone defects. However, assessment of perfusion is challenging, as clinical examination is difficult intra-operatively and often not possible post-operatively. Therefore, it is important to develop techniques to assess perfusion of vascularized bone flaps, and potentially improve surgical outcomes. Near-infrared (NIR) fluorescence imaging has been previously shown to provide real-time, intra-operative evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…To the authors' knowledge, this has not been described previously within human clinical models, but this concept has been proved within animal studies by Nguyen et al 30 The ability to objectively assess these tissue structures has clear ramifications in the design and harvest of the bone and composite flaps. The authors were able to better design their osteotomies when sectioning the fibula to create mandibular constructs.…”
Section: Discussionmentioning
confidence: 96%
“…To the authors' knowledge, this has not been described previously within human clinical models, but this concept has been proved within animal studies by Nguyen et al 30 The ability to objectively assess these tissue structures has clear ramifications in the design and harvest of the bone and composite flaps. The authors were able to better design their osteotomies when sectioning the fibula to create mandibular constructs.…”
Section: Discussionmentioning
confidence: 96%
“…Our laboratory has previously demonstrated real‐time intraoperative NIR fluorescence angiography as a means of determining perforator location in addition to flap perfusion . NIR angiography has also been evaluated for the detection of flow changes following graded experimental arterial stenosis in a rodent model with encouraging results .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies demonstrate the utility of NIR fluorescence as a comprehensive tool for guidance during tissue flap transplantation. Further study will be necessary to determine optimal use in evaluating other flaps, such as muscle; although pilot studies have examined use in vascularized bone flaps …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our group has demonstrated that NIR imaging can provide real-time, intraoperative assessment of bone perfusion. [30]…”
Section: Discussionmentioning
confidence: 99%